Analysis of households food insecurity and its coping mechanisms in Western Ethiopia - Seid Sani; Biruk Kemaw (Agricultural and Food Economics, 2019)
This study analyzed households' food insecurity and its determinants along with the coping mechanisms opted against food insecurity and shortage in Assosa zone, western Ethiopia. The study used a primary data collected from 276 randomly selected households for 7 consecutive days from each sample using weighed records method. In addition, focus group discussions and key informants interview were also used. This study employed descriptive statistics, food insecurity index and Tobit model to analyze the data. The finding of the study revealed that, in the study area, the incidence of food insecurity was 53.62%, with the depth and severity of food insecurity being 16.84% and 7.32%, respectively. The study finding also pointed out that the mean kilocalorie intake of food insecure households was 1440.37kcal/AE/day, with the minimum and maximum being 597.65 kcal and 2048.13 kcal, respectively. Furthermore, the estimated Tobit model result revealed that age of the household head, family size and off-farm and non-farm income positively affected extent of households food insecurity; whereas access to irrigation, farm income, distance to market and access to credit negatively affected the extent of households' food insecurity. Moreover, the study also identified that reducing meal size, reducing frequency of meal served, working as a daily laborer and selling livestock's were the top four main coping mechanisms opted against food insecurity and/or shortage. Therefore, to reverse the incidence, future interventions should focus on the aforementioned factors to build the capacity of households through enhancing their access to human, financial and physical capital.
Keywords: 330; Food insecurity; Coping mechanism; Tobit model; Assosa zone; Ethiopia